A triptycene-based enantiopure bis(diazadibenzoanthracene) by a chirality-assisted synthesis approach [data] - Wang, Xubin; Kohl, Bernd; Rominger, Frank; Elbert, Sven; Mastalerz, Michael (Universität, 2022)
By applying a chirality-assisted synthesis (CAS)approach enantiopure diaminodibromotriptycenes were converted to rigid chiral helical diazadibenzoa...
Gesehen am 08.03.2022
Keywords: Forschungsdaten; Datenbank